The Newest Member of the Family of Chloralose: Synthesis of β-Ribochloralose and Some Derivatives - Kadir Ay; Erkan Halay (Journal of Chemistry)
Treatment of D-ribose with chloral in the presence of acid catalyst gives 1,2-O-(S)-trichloroethylidene-α-D-ribofuranose (1) (β-ribochloralose). Some derivatives of this product (1) were synthesized to be used as an intermediate in carbohydrate chemistry. Tricyclic orthoester structure (3, 77%) was obtained from the reaction of 1 with potassium t-butoxide. This novel orthoester is expected to be useful as a glycosyl donor in the formations of new ribofuranoside units. 3-O-Methyl-ribochloralose (5) was synthesized in 75% yield via the methylation of 1. 5-O-Tosyl-ribochloralose (6, 61%) was prepared with monotosylation reaction of 1. Treatment of 6 with NaN3 in DMF gives a 5-azido-5-deoxy-ribochloralose (7) in 77% yield. The azidosugar (7) was reduced to 5-amino-5-deoxy-ribochloralose (8, 72%) with triphenylphosphine according to Staudinger’s reduction procedure.